The Application of Restorative Justice with an Integrated System in Handling Minor Crimes: A Legal Certainty Perspective - Mas Putra Zenno Januarsyah; Aji Mulyana; Grace E. Tambun; Salsabila Hadi Aulia; Nizar Taufik Setiawan (Proceeding International Conference on Social Sciences, 2026)
The application of restorative justice focuses on restoring the relationship between victims and offenders and repairing the harm caused, aligning with the function of criminal law as the ultimum remedium for minor offences. This study aims to analyse the synchronisation of Restorative Justice implementation within the Integrated Criminal Justice System and its implications for legal certainty. Using a normative legal research method with legislative and conceptual approaches, this study examines formal regulations across police, prosecution, and court institutions, as well as criminal law doctrines. The implementation of restorative justice in minor offence cases reflects a paradigm shift from retributive to reparative justice, emphasising social restoration. Although current regulations have established procedural certainty for case termination discretion, dilemmas persist within the trichotomy of justice, certainty, and utility. The consensus-based nature of restorative justice may undermine legal certainty if law enforcement discretion lacks uniformity. Therefore, to maintain system integrity, regulatory unification at the statutory level and reinforcement of substantive legal certainty are necessary where certainty is assessed through the realisation of justice responsive to social values and victim recovery. Strengthening restorative justice as an accountable diversion mechanism is essential to achieving balanced legal objectives that prioritise justice and utility without compromising the integrity of the legal system.